2021
DOI: 10.1037/dev0001159
|View full text |Cite
|
Sign up to set email alerts
|

Development of shyness across adolescence: Reactivity, regulation, or both?

Abstract: The reactivity-regulation model suggests that the origins and maintenance of shyness results from relatively high levels of reactivity in combination with relatively low levels of regulation. Although this model has received some empirical support, there are still issues regarding directionality of the relations among variables and a dearth of studies examining the joint influence of reactivity and regulation on the prospective development of shyness. Using a longitudinal design, we first examined whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
(130 reference statements)
1
13
0
Order By: Relevance
“…The purpose of present study was to empirically examine whether the approach-avoidance motivational conflict model of shyness described by Asendorpf (1990) predicted the longitudinal development of shyness from late childhood to adolescence (Study 1) 1 and from emerging adulthood to young adulthood (Study 2). Using growth curve analyses, we examined whether the approach-1 Study 1 used the same archival dataset recently used, and reported on, in Hassan et al (2021). In that study, we explored the interaction and directionality of temperament in relation to the growth of shyness, a conceptually different question to the present study in which we explore here the role of motivational tendencies and motivational conflict in predicting the development of shyness.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of present study was to empirically examine whether the approach-avoidance motivational conflict model of shyness described by Asendorpf (1990) predicted the longitudinal development of shyness from late childhood to adolescence (Study 1) 1 and from emerging adulthood to young adulthood (Study 2). Using growth curve analyses, we examined whether the approach-1 Study 1 used the same archival dataset recently used, and reported on, in Hassan et al (2021). In that study, we explored the interaction and directionality of temperament in relation to the growth of shyness, a conceptually different question to the present study in which we explore here the role of motivational tendencies and motivational conflict in predicting the development of shyness.…”
Section: The Present Studymentioning
confidence: 99%
“…1Study 1 used the same archival dataset recently used, and reported on, in Hassan et al (2021). In that study, we explored the interaction and directionality of temperament in relation to the growth of shyness, a conceptually different question to the present study in which we explore here the role of motivational tendencies and motivational conflict in predicting the development of shyness.…”
mentioning
confidence: 99%
“…The finding that nonemotion self-regulation was associated with prospective prosocial tendencies is largely in line with the extant literature. Numerous studies have examined the relation between self-regulation and prosociality and found positive associations 1 Results remained unchanged when using the shyness measure recently reported in Hassan et al (2021).…”
Section: Nonemotion Self-regulation and Prosocial Tendenciesmentioning
confidence: 99%
“…1Results remained unchanged when using the shyness measure recently reported in Hassan et al (2021).…”
mentioning
confidence: 93%
“…Shyness is a characteristic of temperament or personality that reflects a tendency to feel anxious and inhibited in anticipation of or during social situations (Cheek & Melchior, 1990) and has been investigated in western cultures for many decades (see Coplan et al, 2021; outcomes and are considered to be a risk factor for poorer socioemotional development and overall well-being (Caspi et al, 1988;Schmidt et al, 2017). For example, shyness in young adults has been associated with higher levels of internalizing problems such as social anxiety or social anxiety disorder (Henderson & Zimbardo, 2010;Poole et al, 2017) and depression or mood disorders (Alfano et al, 1994;Murberg, 2009;Schmidt & Fox, 1995) as well as with higher levels of negative emotionality and lower levels of selfregulation, dispositional characteristics proposed to be problematic for adaptive social functioning (see Eisenberg et al, 1995 andHassan et al, 2021). In addition, adults with relatively higher versus lower levels of shyness were more likely to experience a poorer relationship with their parents, friends, or romantic partners, and enter into marriage at an older age, experience more severe marital problems, or express lower marital satisfaction (Baker & McNulty, 2010;Caspi et al, 1988;Nelson et al, 2008).…”
mentioning
confidence: 99%